The life of understanding : a contemporary hermeneutics - Risser, James, 1946- (Studies in Continental thought., 2012)
In Gadamer's hermeneutics, interpretation is inseparable from the broader concern of making one's way in life. In this book, James Risser builds on this insight about the juxtaposition of human living and the act of understanding by tracing hermeneutics back to the basic experience of philosophy as defined by Plato. For Risser, Plato provides resources for new directions in hermeneutics and new possibilities for "the life of understanding" and "the understanding of life." Risser places Gadamer in dialogue with Plato, with the issue of memory as a conceptual focus. He develops themes pertaining.